1990
DOI: 10.1177/089686089001000124
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis following Colonoscopy in a Peritoneal Dialysis Patient

Abstract: A 65-year-old woman on continuous ambulatory peritoneal dialysis (CAPD) developed blood-tinged dialysate and bacterial peritonitis following a colonoscopic polypectomy. She grew multiple anaerobic organisms in her dialysate despite antibiotic prophylaxis with vancomycin and gentamicin prior to the procedure. This case confirms the need for broad spectum antibiotic prophylaxis prior to colonoscopic procedures, especially if polypectomy is planned. The antibiotic chosen should cover anaerobes as well as gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
0
21
1
Order By: Relevance
“…Patients on peritoneal dialysis may be at risk for infectious complications after colonoscopy. There are several reported cases of peritonitis in patients on peritoneal dialysis after colonoscopy especially postpolypectomy [45,46]. The International Society for Peritoneal Dialysis (ISPD) in 2005 recommended prophylactic antibiotics and emptying the peritoneal fluid before colonoscopy; however 2010 ISPD recommendations did not address these prevention strategies [47,48].…”
Section: Infectionmentioning
confidence: 99%
“…Patients on peritoneal dialysis may be at risk for infectious complications after colonoscopy. There are several reported cases of peritonitis in patients on peritoneal dialysis after colonoscopy especially postpolypectomy [45,46]. The International Society for Peritoneal Dialysis (ISPD) in 2005 recommended prophylactic antibiotics and emptying the peritoneal fluid before colonoscopy; however 2010 ISPD recommendations did not address these prevention strategies [47,48].…”
Section: Infectionmentioning
confidence: 99%
“…There exists a lack of consensus on this issue. There have been few case reports in the literature on peritonitis following colonoscopy in peritoneal dialysis patients [6,7,[12][13][14][15]. These reports suggested that instrumental procedures such as colonoscopy may precipitate gram negative peritonitis in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is still the fourth leading cause of cancer related death in the world [1]. Although controversial, the overall incidence of cancer is reported to be higher in patients with ESRD than in the general population [2][3][4][5][6][7][8]. Unfortunately, no studies have documented the rate of colorectal cancer among patients with end stage renal disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Risk is further increased by comorbid conditions such as diabetes mellitus 3 . The incidence of postcolonoscopy peritonitis without prophylaxis in two large studies, was 6.3% and 6.4%, respectively, 5,6 and was three‐ to fivefold higher if polypectomy was performed 4,7–9 . Multiple single‐center studies that showed a reduction in peritonitis of as much as 100% post‐GI/GU procedures with prophylactic antibiotics vs no prophylaxis 1–3 .…”
Section: General Risks Of Abdominal Surgerymentioning
confidence: 99%